Peran Agama dalam Mengatasi Kecemasan Masyarakat Terkait Pandemi Covid-19 - Nur Amelia; Siti Rahmah; Satika Nomitama Harahap (Universitas Islam Negeri Sumatera Utara, 2021)
ABSTRACT. Research on the Role of Religion in Addressing CommunityAnxiety related to the Covid-19 Pandemic was conducted from 18 July 2020 - 17August 2020. This study aims to examine the role of religion in overcomingsociety regarding the COVID-19 pandemic. The subjects in this study were 14people from various regions in North Sumatra. The research used a methodbased on data purposive sampling, namely the selection of samples based on factson the sample with the aim of obtaining data that was in accordance with thepurpose of the study. The results show that total respondents have complaintsabout the Covid-19 pandemic. Where is the anxiety that arises when hearingabout the development of the Covid-19 case and the increasingly widespreadspread of the Covid-19 pandemic. Then, from the data obtained, it is also knownthat all respondents can overcome their anxiety by carrying out religious ordersand sticking to religion. Keywords: anxiety, covid-19 pandemic, role of religion.